Fifth IEEE International Conference on Advanced Learning Technologies (ICALT'05) 2005
DOI: 10.1109/icalt.2005.32
|View full text |Cite
|
Sign up to set email alerts
|

A virtual predictive keyboard as a learning aid for people with neuro-motor disorders

Abstract: In India, the population with severe neuro-motor impairments (like people suffering from cerebral palsy) faces an acute problem with electronic-learning because there is a dearth of quality learning aids available for them. By quality learning aids we mean certain softwares that can help this section of special users to learn fast and at the same time with ease. Though similar systems are available in the international market, all of such products have a cost ranging from a few hundred to a few thousand dollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The layout was a modification of the soft keyboard reported in Mukherjee et al (2005). We refer to the three SKs resulted from the Bengali layout as B 3 (the keyboard with 3-level scanning), B 2 (the keyboard with 2-level scanning) and B 1 (the keyboard with 1-level scanning) in subsequent discussions.…”
Section: Interfaces and Access Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The layout was a modification of the soft keyboard reported in Mukherjee et al (2005). We refer to the three SKs resulted from the Bengali layout as B 3 (the keyboard with 3-level scanning), B 2 (the keyboard with 2-level scanning) and B 1 (the keyboard with 1-level scanning) in subsequent discussions.…”
Section: Interfaces and Access Switchesmentioning
confidence: 99%
“…User trials are subsequently conducted to determine efficacy of the resulting design. Jones (1998) and Mukherjee et al (2005) reported examples of this design approach. Some researchers reported more systematic model based design approaches.…”
Section: Introductionmentioning
confidence: 99%